TINGKAT PENGETAHUAN SINDROM FEMALE ATHLETE TRIAD (FAT) : STUDI PENDAHULUAN - Itsna Rosyada; Sapta Kunta Purnama; Budiyanti Wiboworini (Universitas Negeri Malang, 2022)
AbstractThe purpose of this preliminary study is to determine the level of knowledge of female pencak silat athletes in Indonesia about the Female Athlete Triad (FAT) syndrome. FAT is linked to three health problems: eating disorders, irregular menstrual function, and low bone density. This condition is common in female athletes who compete in sports that require weight categorization as part of the competition regulations. Data was collected using a cross-sectional technique, with online surveys distributed to 82 female pencak silat athletes in Lamongan, Surabaya, and Solo. The findings of the study indicated that female pencak silat athletes had a low level of knowledge about FAT, with (30 point 49 percent) had no knowledge of FAT before this research was conducted and (69 point 51 percent) already knowing FAT from the distribution of FAT education on social media managed by researchers, while being unable to explain the relationship between FAT components properly. Given the complexities of the FAT syndrome, FAT-based health management changes are required in order to prevent the long-term repercussions of FAT and increase female athletes performance in pencak silat.Keywords: female athlete triad; menstrual function; pencak silatAbstrakStudi pendahuluan ini bertujuan untuk menginvestigasi tingkat pengetahuan atlet putri pencak silat Indonesia mengenai sindrom Female Athlete Triad (FAT). FAT adalah keterkaitan antara tiga gangguan kesehatan, yaitu gangguan makan, abnormal fungsi menstruasi dan penurunan densitas tulang. Sindroma ini banyak ditemukan pada atlet putri pada cabang olahraga yang menggunakan klasifikasi berat badan dalam peraturan pertandingannya. Pengambilan data dilakukan menggunakan metode potong lintang dengan penyebaran kuesioner online terhadap 82 atlet putri pencak silat di Kabupaten Lamongan, Kota Surabaya dan Kota Solo. Hasil penelitian ini, diketahui bahwa tingkat pengetahuan atlet putri pencak silat terkait FAT terbilang rendah, dimana (30 koma 49 persen) responden belum mengetahui FAT sebelum penelitian ini dilakukan dan (69 koma 51 persen) responden telah mengetahui dari sebaran edukasi FAT pada sosial media yang dikelola peneliti, tetapi tidak dapat menjelaskan hubungan antar komponen FAT dengan baik. Mengingat kompleksnya sindrom FAT, perbaikan manajerial kesehatan berbasis FAT diperlukan sebagai upaya pencegahan konsekuensi jangka panjang FAT dan peningkatan performa tanding atlet putri pencak silat Indonesia. Kata kunci: female athlete triad;fungsi menstruasi; pencak silat